Сезонная изменчивость хлорофилла и биомассы фитопланктона в западной части Черного моря - Берсенева, Г. П.; Чурилова, Т. Я.; Георгиева, Л. В. (My University, 2004)
Представлены результаты двухлетнего непрерывного Мониторинга по определению содержания хлорофилла “а” и биомассы фитопланктона в центральной западной части и в районе склона континентального шельфа Черного моря. Сезонная динамика концентрации хлорофилла “а” в обоих регионах соответствует U-образному типу. Она характеризуется низкими летними значениями и высокими - в осенний период, которые переходят в зимне-весеннее “цветение” фитопланктона. Амплитуда средних значений концентрации хлорофилла равна 3-4 в центральной части моря и около 2 - в районе континентального склона. В разные годы высокие значения биомассы фитопланктона в осенне-зимне-весенний период обусловлены как типичным “цветением” диатомовых водорослей, так и другими таксонами. В центральной западной части моря отмечена связь между относительным содержанием феопигментов и концентрацией хлорофилла. Установлена сезонная динамика отношения углеродной биомассы фитопланктона к хлорофиллу “а”. Осенне-зимне-весенние показатели составляли в среднем 20, а летние - 40-50 в обоих исследованных районах.
Seasonal Variability of Chlorophyll and Phytoplankton Biomass in the Western Part of the Blask Sea
The data of two-year-long continuous monitoring carried out in the central part of the Black Sea and in the slope zone of its continental shelf for determination of the chlorophyll a concentration and phytoplankton biomass are presented. The seasonal trend of the chlorophyll a concentration in both areas corresponds to a U-shaped-type. It is characterized by low values in the summer and high values during the fall period; the latter transfers into the winter-spring phytoplankton bloom. The amplitude of the mean values of the chlorophyll concentration varies from 3 to 4 in the central part of the sea and is equal to about 2 in the area of the continental slope. During different years, the high values of phytoplankton biomass over the fall-winterspring period are due to the typical bloom of diatoms and to other taxa. In the central part of the Western Black Sea, the relationship between the relative content of phaeopigments and the values of chlorophyll concentration was determined. The seasonal dynamics of the carbon biomass-chlorophyll a concentration ratio was revealed. In both of the research areas, the fall-winter-spring mean values of this parameter were equal to 20, while those in the summer varied from 40 to 50.